Enhancing Vocational Education in Egypt: The Role of Project-Based Learning in Developing 21st-Century Skills - Nisa Ulaini; Azmi Fitrisia (STAI Hubbulwathan Duri, 2025)
In the era of globalization and technological advancements, 21st-century skills—such as critical thinking, collaboration, creativity, and problem-solving—are essential for vocational high school students. This study examines the effectiveness of Project-Based Learning (PjBL) in fostering these competencies within Egypt’s vocational education system. A qualitative research approach was employed, utilizing in-depth interviews with educators and an analysis of student project outcomes. Data collection focused on assessing how PjBL influences students’ skill development and the challenges associated with its implementation. Findings indicate that PJBL significantly enhances not only students' technical expertise but also their adaptability and critical thinking skills, preparing them for the evolving labor market. Additionally, institutional support and continuous professional development for educators emerged as key factors in ensuring effective PJBL integration. These results highlight the potential of PJBL as an innovative pedagogical approach aligned with Egypt’s ongoing educational reforms. By fostering essential 21st-century skills, PJBL can better prepare vocational students for the workforce. However, successful implementation requires strategic institutional backing and teacher training. PjBL is a valuable instructional strategy for modernizing vocational education in Egypt. Its broader application could contribute to global educational advancements, equipping students with the competencies needed in a dynamic, interconnected world. This study adds to the discourse on enhancing vocational education through active, skill-oriented learning methodologies.